Regard sur la dynamique ethno-sociolinguistique actuelle de la Provence, ou quand l’identité fait reculer la diglossie - Philippe Blanchet (La Bretagne Linguistique, 1998)
After a brief history of the sociolinguistic situation in Provence, the author presents the linguistic realities of the region. He recalls the diglossic situation prevalent in this territory and gives numerous examples of linguistic practices before highlighting future prospects.